PRARANCANGAN PABRIK ASETALDEHID DARI ETILENA KAPASITAS 45.000 TON / TAHUN - , DIAH LIDYAWATI; , Dr.Ir.Bardi Murachman,S.U., D.E.A ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The acetaldehyde plant from ethylene and oxygen will be designed with capacity 45000 ton/year. The product is acetaldehyde with 99,9% purity and Acetic acid with 0,4 % purity. This plant runs for 330 days/year. The raw material is ethylene with 99% purity and oxygen with 99,5 % purity .The reaction occurs at 90-126OC with 3 atm in in a bubble reactor containing a catalyst of palladium chloride dissolved in water. This plant will be established in Cilegon, Banten with 40.000 m2 land area and 155 employees. This plant needs 33481,228 kg/year ethylene, 19749.0228 tons / year oxygen , and a catalyst as much as 12 kg / year. For utility, this plant needs 336,377 m3/year water, 4.110,8927 m3/year fuel oil, and 800 kVA electricity. The fixed capital is US$ 10.173.198,36 and Rp 30.429.828.683. The working capital is Rp. 65.367.393.445,87. The profit before tax is Rp 39.278.708.862,64 and the profit after tax is Rp 19.639.354.431,32. From the feasibility calculation, we know that the ROI (Return of investment) before tax is 32,20 % and ROI after tax 16,10%, the POT (Payout Time) before tax is 2,37 years , the POT after tax is 3,83 years, BEP (Break even point) is 49,92 %, SDP is 31,40%, and DCFRR is 25,18%. According to the calculation of economic evaluation, so acetaldehyde plant with 45000 ton/year capacity is interesting to be reviewed further.